Development of PBL E-Module on the Role of Nyale Worms in Coral Reef Ecosystems to Increase Learning Interest and Critical Thinking among High School Students - Mawaddah Fatin Nuradiah; Fhadinda Hizza Raphasya; Era Mutiara; Muhammad Fikri Alfiansyah; Suyitno Aloysius; Nurul Izzurrahmah (Journal of Science Education Research, 2026)
This study aims to develop a Problem-Based Learning (PBL) e-module with a flipped classroom approach that is valid, Applicable, and effective in enhancing the learning interest and critical thinking skills of Phase E students on the ecosystem topic, particularly the role of nyale worms in coral reef ecosystems. Using the ADDIE development model, the study was conducted at MAN 2 Mataram with 63 students selected through cluster random sampling, where class X-11 served as the experimental group and class X-9 as the control group. The research instruments included expert validation questionnaires, Applicable assessments, critical thinking tests, and learning interest questionnaires. The results indicated that the developed e-module: (1) is valid according to media and content experts, (2) highly Applicable based on evaluations by teachers and students, and (3) effective in increasing learning interest and critical thinking skills, as evidenced by MANOVA analysis. Integrated into the PBL model, the e-module combines local potential with a flipped classroom strategy, offering students an engaging, interactive, contextual, and meaningful learning experience. Based on the research findings, the flipped classroom PBL e-module on the role of nyale worms in coral reef ecosystems is concluded to be feasible, highly Applicable, and effective in enhancing both learning interest and critical thinking skills among Phase E students in ecosystem learning.